The Benefits of Mine Scale Three-Dimensional Structural Modelling at Macraes Mine, Central Otago – A Case Study - A J. Daniels (The Australasian Institute of Mining and Metallurgy, 2011)
Macraes Mine is a large-scale open-cut and underground gold mine located in Central Otago, on the South Island of New Zealand. This paper presents the role of geological mapping in the grade control process at Macraes Open Pit as a case study, and demonstrates how systematic geological mapping can add significant value to the mining cycle. Geological mapping has proved to be a valuable foundation for orebody interpretation and analysis.Practical applications and lessons learnt are summarised, including predictive control of the orebody, improvement of geotechnical modelling, and identification of further exploration targets.